Using high-immersion social virtual reality environments for researching interculturality - Jauregi-Ondarra, Kristi; Meijerink, Juul; Christoforou, Maria (My University, 2024)
Virtual reality (VR) has rapidly evolved as a language education environment, offering opportunities for immersion, interactivity, and enhanced motivation for learners. High-immersion social virtual reality (HISVR) holds great potential for language learning due to its immersive experiences, embodied interaction, and opportunities for international telecollaboration and intercultural learning. This chapter investigates intercultural communication within HISVR from a multimodal interactional perspective. Through a case study, we scrutinize how VR technology can contribute to the examination of students’ intercultural negotiation during HISVR-mediated virtual exchanges, aiming to deepen our understanding of intercultural communication in HISVR environments. We introduce an innovative research approach that investigates how learners participate in ‘blocking and threading narratives’ within these exchanges and apply multimodal interaction analysis to this study. This research seeks to enrich the evolving landscape of studies on intercultural communication in VR-enhanced environments.
Keywords: High-immersion social virtual reality (HISVR); Intercultural communication